2021
DOI: 10.3390/land10121324
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Revealing of Traditional Settlements and Cultural Assets, as a Tool for Sustainable Development: The Case of Kythera Island in Greece

Abstract: Preserving and highlighting cultural heritage is directly related to sustainable development. The adaptive reuse of cultural heritage buildings and traditional settlements can be a core issue in the implementation of a circular economy strategy, especially in remote areas. In this framework, the current study focuses on Kythera, an isolated Greek island. For the analysis of the study area, research in local archives and communication with the municipality and local stakeholders was conducted, while questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Over the decades, studies on heritage tourism have provided diverse and highly segmented studies on different topics including heritage tourists [5], heritage experience [6], and experience stages of heritage tourism [7]. Recently, many studies have discussed that the inner factors and co-creation of tourists can largely influence heritage experience [8][9][10] and heritage protection [11]. This confirms the impact of tourist initiatives on tourism experience and heritage management.…”
Section: Introductionmentioning
confidence: 80%
“…Over the decades, studies on heritage tourism have provided diverse and highly segmented studies on different topics including heritage tourists [5], heritage experience [6], and experience stages of heritage tourism [7]. Recently, many studies have discussed that the inner factors and co-creation of tourists can largely influence heritage experience [8][9][10] and heritage protection [11]. This confirms the impact of tourist initiatives on tourism experience and heritage management.…”
Section: Introductionmentioning
confidence: 80%
“…Various RCP solutions that embody the idea of reviving past or almost lost practices, or searching for alternative options, are often driven by identity and/or new business models. Some studies see cultural heritage buildings as rural attractions, which can lead to more tourism and income, and increased employment through the rehabilitation, maintenance, and repurposing of underused buildings [16,33,34]. These practices embody the idea of slowing down and extending the lifetime of existing buildings and infrastructure.…”
Section: Rural Circularity Practices: Ongoing Practices and Opportuni...mentioning
confidence: 99%
“…Traditional settlements are shaped by topography and the natural environment, giving specific distribution, scale, hierarchy, and morphology (Li et al, 2018;Tao et al, 2017). The socio-economic development of a traditional settlement is deeply related to people"s social, cultural, and economic dimensions, and people"s collective activity constructs its significance, configured by geographical, geomorphological, and spatial criteria (Vythoulka et al, 2021). Many researchers have concluded that most socio-economic development-led design interventions have isolated buildings and places from social-cultural-economic significance instead of connecting them, and those transformations affect the settlements" morphology, natural resources, and infrastructure needs (Hes, Hernandez-Santin, et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%